Equations of phase-locked loops : dynamics on circle, torus and cylinder - Kudrewicz, Jacek (World Scientific series on nonlinear science. Monographs and treatises, 2007)
"Phase-Locked Loops (PLLs) are electronic systems that can be used as a synchronized oscillator, a driver or multiplier of frequency, a modulator or demodulator and as an amplifier of phase modulated signals. This book updates the methods used in the analysis of PLLs by drawing on the results obtained in the last 40 years. Many are published for the first time in book form."--Jacket